Corruption and crisis: Do institutions matter? - Shrabani Saha; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
While the short-term effects of the COVID-19 pandemic on lives and livelihoods are well understood, we know little about the effect of the pandemic for longer-term outcomes such as corruption. We look at the historical data on political and economic crises to assess what we can learn from the long-term effects of past crises on corruption. We hypothesize that strong rule of law institutions may ameliorate the possible adverse effects of political and economic crises on corruption. We test our hypotheses using panel data for over 100 countries during the years 1800- 2020. The results suggest heterogeneous effects depending on the type of crisis and how we measure it. We find that rule of law institutions can control corruption in cases of political violence and economic slowdown, but the effect is not seen for democracy breakdowns, coups, armed conflict and civil war, and economic crisis such as currency and debt crisis.
Keywords: K42; O11; P48; 330; corruption; institutions; political and economic crises; panel data; rule of law